2023
DOI: 10.1253/circrep.cr-22-0076
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Re-Evaluation of Edoxaban and Rivaroxaban Dosing With Plasma Concentration Monitoring in Non-Valvular Atrial Fibrillation: With Observations of On-Label and Off-Label Dosing

Abstract: Background: Off-label dosing of direct oral anticoagulants (DOAC) as a treatment for non-valvular atrial fibrillation (NVAF) is problematic. Here, we investigated the status of rivaroxaban and edoxaban dosing by monitoring plasma concentrations (PCs). Methods and Results:We monitored drug PCs in 391 and 333 outpatients receiving rivaroxaban and edoxaban, respectively, for NVAF. Drug doses were adjusted if the PC was above the cut-off value (rivaroxaban: 404 ng/mL; edoxaban: 402 ng/mL), determined from receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…We indicated that rivaroxaban had a high incidence of bleeding events, and plasma concentration in peak samplings measured with anti-FXa chromogenic assay showed higher levels in rivaroxaban compared with edoxaban dosing. 2 We had the same results when switching from rivaroxaban to edoxaban in the same patients, including elderly participants. 2 As mentioned previously, plasma concentration–directed dose adjustment has been shown to be helpful in controlling outcomes and prevented unnecessary bleeding events in NOAC dosing, even off-label dosing.…”
Section: To the Editormentioning
confidence: 57%
See 3 more Smart Citations
“…We indicated that rivaroxaban had a high incidence of bleeding events, and plasma concentration in peak samplings measured with anti-FXa chromogenic assay showed higher levels in rivaroxaban compared with edoxaban dosing. 2 We had the same results when switching from rivaroxaban to edoxaban in the same patients, including elderly participants. 2 As mentioned previously, plasma concentration–directed dose adjustment has been shown to be helpful in controlling outcomes and prevented unnecessary bleeding events in NOAC dosing, even off-label dosing.…”
Section: To the Editormentioning
confidence: 57%
“…2 We had the same results when switching from rivaroxaban to edoxaban in the same patients, including elderly participants. 2 As mentioned previously, plasma concentration–directed dose adjustment has been shown to be helpful in controlling outcomes and prevented unnecessary bleeding events in NOAC dosing, even off-label dosing. 2,3 When using oral anticoagulants, many bleeding and thromboembolic events occurred.…”
Section: To the Editormentioning
confidence: 57%
See 2 more Smart Citations